2020
DOI: 10.1186/s12935-020-01402-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FOXD3-AS1 promoted chemo-resistance of NSCLC cells via directly acting on miR-127-3p/MDM2 axis

Abstract: Background: This study aims to investigate the mechanism underlying the high level of long non-coding RNA FOXD3-AS1 in cisplatin-resistant NSCLC cells. Methods: Cisplatin-resistant cells were generated from A549 cells. CCK-8 were used to evaluate cell proliferation. The FOXD3-AS1, miR-127-3p, MDM2 and MRP1 mRNA expression levels were confirmed by qRT-PCR. Protein levels of MDM2 and MRP1 were determined by western blot assay. Luciferase reporter and RNA pull-down assays were evaluated the relationship between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…LncRNA FOXD3-AS1 has been identified as high expression in a variety of cancers ( 29 , 30 ). In cervical cancer, the expression of FOXD3-AS1 is significantly increased and associated with poor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA FOXD3-AS1 has been identified as high expression in a variety of cancers ( 29 , 30 ). In cervical cancer, the expression of FOXD3-AS1 is significantly increased and associated with poor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence also indicates that FOXD3-AS1 is closely associated with poor prognosis in patients with NSCLC and plays an oncogenic role. Indeed, FOXD3-AS1 is involved in the pathological cell activities and chemo-resistance of NSCLC by sponging miR-127-3p to modulate MED28 or MDM2 expression, respectively ( 17 , 18 ). However, the role of FOXD3-AS1 in NSCLC remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, FOXD3-AS1 has also been confirmed to play an important role in NSCLC. For instance, FOXD3-AS1 promotes cisplatin chemoresistance of NSCLC cells by directly acting on the miR-127-3p/MDM2 axis ( 17 ). High expression levels of FOXD3-AS1 promote NSCLC progression by regulating the miR-127-3p/mediator complex subunit 28 (MED28) axis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin can act through lncRNAs that regulate disease progression in lung cancer by sponging miRNAs, whose interaction with lncRNAs modulates a variety of genes in cancer apoptosis, migration, proliferation and resistance [37][38][39][40][41][42]. As the role of lncRNAs in the anticancer effect of monofunctional platinum(II) complexes had not yet been assessed, we used microarray analysis to identify regulated lncRNAs in A549 and IMR90 cells after treatment with cisplatin or phenanthriplatin.…”
Section: Discussionmentioning
confidence: 99%